ANALISA PERBANDINGAN PENEMPATAN DINDING GESER PADA BANGUNAN GEDUNG BERTINGKAT MENGGUNAKAN SNI 1726-2019 - Tito Bobby Kristianto; Maryanto Maryanto; Frieda Frieda (Fakultas Teknik Universitas Palangka Raya, 2025)
Areas in Indonesia are prone to earthquakes, so it is necessary to plan a structure that can withstand the lateral forces caused by the earthquake. Shear walls are very effective in resisting lateral forces due to their high stiffness. The purpose of the study was to determine the effect of the location of shear walls on structures subjected to earthquake loads according to SNI 1726-2019. 7 structural models were created, namely 1 model without a shear wall and 6 models plus a shear wall with the same area and location which were divided into 2 models each in the core area, transition area and edge area and analyzed with software ETABS. Results of analysis are time period, story drift and moments of column in all models are then compared. Obtaining the value of the small time period by placing the shear wall at the edge of the building, with the highest stiffness value. Obtain the value of the story drift in the direction of the small long axis by placing a shear wall in the core area of the building, with a relatively small stiffness value. While value of the short axis deviation story drift by placing a shear wall in the transition area with a small stiffness. Small column moments value by the location of the shear wall in the transition area has the smallest maximum column moment value with a relatively small stiffness. The rigidity of the frame structure is greatest by placing shear wall at the edges of the building.